Batman: abyss - Williamson, Joshua 1981-; Molina, Jorge 1984-; Porter, Howard (DC Comics, 2022)
"While unraveling a mystery that involves his closest allies, Batman will come to face-to-face with a new villain who turns the darkness into his greatest threat. As Gotham celebrates surviving Fear State, Batman retreats alone into the darkness. But when he learns of a mystery involving Batman Inc., it forces the Caped Crusader to leave Gotham for a brand-new adventure! He'll discover Batman Inc.'s mysterious new benefactor and clash with a brand-new foe who turns Batman's greatest weapon against him. Will Batman be able to save his closest allies or find himself lost in the dark against the Abyss?"--
"Batman created by Bob Kane with Bill Finger - Superman created by Jerry Siegel & Joe Shuster, by special arrangement with the Jerry Siegel family
"This volume collects issues #118-121 and 124 of Batman
Keywords: Batman -- Fiktive Gestalt; Batman / (Fictitious character) / Comic books, strips, etc; Batman / (Fictitious character); Comics (Graphic works); Graphic novels; Superhero comics; Comic